2022
DOI: 10.1109/access.2021.3140074
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sleep Quality Using Mobile EMAs: Opportunities, Practical Consideration, and Challenges

Abstract: Sleep is one of the most important factors in maintaining both physical and mental health. There are many causes of sleep problems, it is generally necessary to maintain a healthy lifestyle to avoid them. In the medical field, information related to sleep problems including lifestyle information is obtained through interviews, but this approach is limited because it is dependent on the patient's memory. Thus, there are many studies adopting ecological momentary assessments (EMAs) to collect patient's lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Six studies collected and examined smartphone data as a proxy indicator of a person’s sleep [ 19 , 51 , 56 , 57 , 58 , 59 ]. Given that a smartphone cannot directly record a person’s sleep, studies used a combination of passively sensed data and user reports to detect sleeping behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies collected and examined smartphone data as a proxy indicator of a person’s sleep [ 19 , 51 , 56 , 57 , 58 , 59 ]. Given that a smartphone cannot directly record a person’s sleep, studies used a combination of passively sensed data and user reports to detect sleeping behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of virulence genes by phylogenetic group [69] . The majority of the virulence factors linked to phylogenetic group B2 have been discovered [70][71][72] . All groups had high levels of the "ecp (A and R-B) and fimH gens (A 100 percent /78.8%, B1 100 percent /70 percent, B2 96.7 percent /91.7 percent, and D 100 percent /100 percent, respectively) [73] .…”
Section: Virulence Factors and Gene That Responsiblementioning
confidence: 99%
“…Especially, combining EMA techniques and machine learning methods is expected to provide reliable sleep measurements in daily life. For instance, a recent study reported that machine learning techniques could estimate daily sleep quality by using complex life data obtained from EMA questionnaires [73]. Collecting and integrating multidimensional information would be meaningful not only in understanding the covariant associations of sleep behavior with daytime symptoms but also for developing novel sleep measurements.…”
Section: Limitationsmentioning
confidence: 99%